Empty sella developing during thyroxine therapy in a patient with primary hypothyroidism and hyperprolactinaemia. Issue 801 (July 1992) - Kelestimur, F.; Selçuklu, A.; Ozcan, N.
Abstract : A 35 year old woman presented with severe primary hypothyroidism and galactorrhea. A very high prolactin level was also detected and computerized tomography scan of the sellar region demonstrated an enlarged pituitary gland associated with contrast enhancement. Replacement therapy with thyroxine corrected both biochemical and clinical abnormalities but empty sella developed during this therapy. It is concluded that empty sella may be related to thyroxine-induced shrinkage of lactotroph and/or thyrotroph cell hyperplasia.